KUALITAS MIKROBIOLOGI NASI JINGGO BERDASARKAN ANGKA LEMPENG TOTAL, COLIFORM TOTAL DAN KANDUNGAN ESCHERICHIA COLI - Yunita, Ni Luh Payastiti; Dwipayanti, Ni Made Utami (Jurnal Biologi Udayana; Vol 14 No 1 (2010): Jurnal Biologi, 2010)
Inadequate quality of food products that do not meet standard quality may lead to food poisoning cases and become a concern in public health sector. Nasi Jinggo is a small amount of cooked rice with little bit fried tempe, shredded spicy chicken, traditional made chili sauce that is packed with banana leaves, and all the cooking process usually done traditionally. Nasi jinggo is sold at night by street vendor with price ranged from Rp. 1.500,- to Rp. 2.000,- per package. The study was a quantitative descriptive study with cross-sectional design that was aimed to identify the microbiology quality of nasi jinggo that were sold in Denpasar Selatan area. From 48 population of nasi jinggo street vendor, 23 vendor was taken as samples. The microbiology quality being assessed was Total Plate Count (TPC), Total Coliform with MPN method and Escherichia coli content with Eosin Methylene Blue Agar as medium. Laboratory analysis showed that only 21,7% sample that met TPC standard with average value of 2,3 x 107 CFU/gram sample, only 8,7% that met Total Coliform standard with average value of 1,4 x 105 MPN/100 gram sample and 52,2% sample that met E. coli content standard with average value is 2,6 x 102 MPN/100 gram sample. It is recommended to the government to do quality check towards nasi jinggo in a regular basis as well as to provide education and assistance to nasi jinggo street vendors in order to improve the microbiology quality of food product and ensure food safety to the consumer.
Keywords: microbiology quality, nasi jinggo, traditional food